MERUMUSKAN PEMIKIRAN EKONOM MUSLIM TENTANG RASIONALITAS DALAM PERILAKU KONSUMEN - Lia Istifhama (Sekolah Tinggi Agama Islam Taruna Surabaya, 2019)
rationality is the characteristic of any action, belief, or desire, that makes their choice optimal under a set of constraints.[1] It is a normative concept of reasoning in the sense that rational people should derive conclusions in a consistent way given the information at disposal. It refers to the conformity of one's beliefs with one's reasons to believe, or with one's actions with one's reasons for action. However, the term